PENGARUH KONDISI FISIK LINGKUNGAN KERJA DAN KEPEMIMPINAN TERHADAP ETOS KERJA PEGAWAI PADA BIRO HUBUNGAN MASYARAKAT KEMENTERIAN LINGKUNGAN HIDUP DAN KEHUTANAN JAKARTA - Zakiyah, Siti Nazla; Sudarijati, Sudarijati (Fakultas Ekonomi Universitas Djuanda, 2017)
The purpose of this research is to analyze the influence of physical conditon of the working environment and leadership to the work ethic of employees at Biro Humas. The respondents in this research consist of 43 employees who work at Biro Hubungan Masyarakat Kementerian Lingkungan Hidup and Kehutanan Jakarta. The result showed that all indicators expressed validity and reliability. The physical condition of the working environment (X1) and leadership (X2) effect the work ethic of employees at Biro Humas(Y). Whereas, partially all the indicators give both positive and significant affect the work ethic of employees at Biro Hubungan Masyarakat.Keywords: physical condition of working environment, leadership, work ethic.